Effectiveness of Corporate Social Responsibility Activities to Changes in Nutritional Status of Children - Sismi Restu Ayuningtyas; Abela Mayunita (Global Health Science Group, 2023)
Corporate Social Responsibility (CSR) has become a central and popular issue in the health sector because it is one of the supporters in implementing health programs that cannot be reached by the government. One program that really needs CSR collaboration is the issue of Nutrition Post for toddlers suffering from malnutrition or lack of nutrition. The purpose of this study is to analyze the effectiveness and significance of CSR programs on improving the nutritional status of toddlers. This study used a retrospective observational method, with case design and control. This research was conducted at UPT Puskesmas Anyar Serang-Banten from January to March 2023. This program is run together with non-government organizations, namely PT. Chandra Asri Cilegon. The sample in this study was 30 toddlers with a proportion of 1: 2, namely 10 toddlers receiving CSR programs suffering from malnutrition and 20 toddlers as a control group. In this study, an analysis of the results of the Nutrition Post CSR program will be carried out with chi square analysis. Based on the results of chi-square analysis, an odds ratio value (OR: 0.4; 95% Confident Interval 0.23 – 0.73; p value 0.001) is produced because p value 0.001 < 0.05.